2011
DOI: 10.1042/bj20102034
|View full text |Cite
|
Sign up to set email alerts
|

Galactose induction of the GAL1 gene requires conditional degradation of the Mig2 repressor

Abstract: Skp1 an essential component of the SCF (Skp1/cullin/F-box) E3 ubiquitin ligases, which target proteins for degradation by the 26S proteasome. We generated a skp1dM mutant strain that is defective for galactose induction of the GAL1 gene and we have found that galactose-induced protein degradation of the repressor Mig2 is defective in this strain. Mig2 degradation was also abolished in cells lacking the protein kinase Snf1 and the F-box protein Das1, suggesting that Snf1 triggers galactose-induced protein degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…This is remarkable because for many years, it has been generally accepted that, in contrast to Mig1, Mig2 is not a substrate for the Snf1 kinase (75, 76). Recent work proposed that galactose induces fast degradation of Mig2 by a mechanism that involves Snf1-dependent Mig2 phosphorylation (77), although it is worth noting that those authors observed an almost complete depletion of Mig2 after only 20 min upon shifting of cells to galactose, whereas in our hands, the amount of Mig2 did not significantly change after 30 min of alkaline stress. In any case, our data support a role for Mig2 in repression of PHO89 expression, and it is reasonable to assume that activation of Snf1 results in a relief of such repression.…”
Section: Discussioncontrasting
confidence: 53%
“…This is remarkable because for many years, it has been generally accepted that, in contrast to Mig1, Mig2 is not a substrate for the Snf1 kinase (75, 76). Recent work proposed that galactose induces fast degradation of Mig2 by a mechanism that involves Snf1-dependent Mig2 phosphorylation (77), although it is worth noting that those authors observed an almost complete depletion of Mig2 after only 20 min upon shifting of cells to galactose, whereas in our hands, the amount of Mig2 did not significantly change after 30 min of alkaline stress. In any case, our data support a role for Mig2 in repression of PHO89 expression, and it is reasonable to assume that activation of Snf1 results in a relief of such repression.…”
Section: Discussioncontrasting
confidence: 53%
“…Snf1 phosphorylates Mig1 (Ostling and Ronne 1998;Treitel et al 1998;Smith et al 1999), which relieves its transcriptional repression function and promotes its export from the nucleus. Mig2 is a functional homolog of Mig1 (Lutfiyya and Johnston 1996), but Mig2 is not regulated by Snf1 and has a localization (Lutfiyya et al 1998;Fernandez-Cid et al 2012) and turnover pattern (Lim et al 2011) that is distinct from Mig1. In high-glucose conditions, Mig1 and Mig2 repress the expression of genes involved in the metabolism of poor carbon sources, in part through Mig1-dependent recruitment of the co-repressor Tup1/Ssn6 (Treitel and Carlson 1995).…”
mentioning
confidence: 99%
“…Phosphorylated Mig2 is ubiquitinated by the E3 ubiquitin ligases SCF Das1/Ufo1 [37]. SNF1 also signals Mediator the absence of glucose via the Snf1-Srb11 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Das1 and Ufo1 (but not Mdm30) also target the repressor Mig2 for galactose-induced protein degradation [37]. However, the additional gene deletion of MIG2 did not increase galactose induction of GAL1 mRNA in the ΔUFO1 strain and had only a very small effect on the galactose induction of the GAL1 mRNA in the ΔDAS1 strain [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation